Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. - Puerta-Piñero, Carolina; Pino, Joan; Gómez, José María (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.
Keywords: Animals; Ecosystem; irradiance; landscape connectivity; Life Cycle Stages; Mediterranean; Passeriformes; Plant Dispersal; Plant–animal interactions; Quercus; Quercus: growth & development; Recruitment; Seedling; Seedling: growth & development; Sus scrofa

Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L; Csoka, G; Nieves-Aldrey, J L (MOLECULAR ECOLOGY, 2001)
The Marble gallwasp Andricus kollari has a native range divided into two geographically separated lifecycles. In Eastern Europe and Turkey, the lifecycle involves a sexual generation on Turkey oak, Quercus cerris, while in Iberia and North Africa the sexual generation host is cork oak, Q. suber. Over the last 500 years, A. kollari has expanded its range into northern Europe, following human planting of Q. cem's from Italy and the Balkans. We ask: (i) what is the genetic relationship between eastern and western distributions of Andricus kollari? Can we determine which lifecycle is ancestral, and how long ago they diverged? (ii) To what extent have eastern and western native ranges contributed to northwards range expansion? (iii) Is there any evidence for hybridization between the two life cycle types? We present analyses of allozyme data for 13 polymorphic loci and of sequence variation for a 433 bp fragment of the mitochondrial cytochrome b gene. These show: (i) that four haplotype lineages (one in Spain, two in Hungary/Italy and one in Turkey) diverged more or less simultaneously between 1 and 2 million years ago, suggesting the existence of at least four refuges through recent ice age cycles. Our data cannot resolve which lifecycle type is ancestral. (ii) Populations north of putative refuges are divided into two sets. Populations in south-west France are allied to Spain, while ail remaining populations in northern Europe have been colonized from Italy and the Balkans. (iii) The transition from one race to another in south-west France is marked by abrupt transitions in the frequency of refuge-specific private alleles and corresponds closely to the northern limit of the distribution of cork oak. Although hybrids were detected in north-west France, none were detected where the two lifecycles meet in south-western France. The biology of oak gallwasps predicts that any hybrid zone will be narrow and limited to regions where Q. cem's and Q. suber meet. Our data suggest that eastern and western A. kollari are effectively separate species.
From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)
Keywords: Alleles; Andricus; Animals; Base Sequence; Cellulose Acetate; Cytochrome b Group; Cytochrome b Group: chemistry; Cytochrome b Group: genetics; DNA; Electrophoresis; Environment; EUROPE; Evolution; Female; gallwasp; Genetic Variation; Genetic Variation: physiology; glacial refugia; host race; Hymenoptera; Hymenoptera: genetics; Hymenoptera: growth & development; Hymenoptera: physiology; invasion; Life Cycle Stages; Mitochondrial; Mitochondrial: chemistry; Mitochondrial: isolation & purification; Molecular; Molecular Sequence Data; Parthenogenesis; phylogeny; Polymerase Chain Reaction; range expansion; Sequence Alignment; Sequence Analysis

Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G.; Atkinson, R.; Rokas, A.; Csoka, G.; Nieves-Aldrey, J. L.; Csoka, G.; Nieves-Aldrey, J. L. (MOLECULAR ECOLOGY, 2001)
The Marble gallwasp Andricus kollari has a native range divided into two geographically separated lifecycles. In Eastern Europe and Turkey, the lifecycle involves a sexual generation on Turkey oak, Quercus cerris, while in Iberia and North Africa the sexual generation host is cork oak, Q. suber. Over the last 500 years, A. kollari has expanded its range into northern Europe, following human planting of Q. cem's from Italy and the Balkans. We ask: (i) what is the genetic relationship between eastern and western distributions of Andricus kollari? Can we determine which lifecycle is ancestral, and how long ago they diverged? (ii) To what extent have eastern and western native ranges contributed to northwards range expansion? (iii) Is there any evidence for hybridization between the two life cycle types? We present analyses of allozyme data for 13 polymorphic loci and of sequence variation for a 433 bp fragment of the mitochondrial cytochrome b gene. These show: (i) that four haplotype lineages (one in Spain, two in Hungary/Italy and one in Turkey) diverged more or less simultaneously between 1 and 2 million years ago, suggesting the existence of at least four refuges through recent ice age cycles. Our data cannot resolve which lifecycle type is ancestral. (ii) Populations north of putative refuges are divided into two sets. Populations in south-west France are allied to Spain, while ail remaining populations in northern Europe have been colonized from Italy and the Balkans. (iii) The transition from one race to another in south-west France is marked by abrupt transitions in the frequency of refuge-specific private alleles and corresponds closely to the northern limit of the distribution of cork oak. Although hybrids were detected in north-west France, none were detected where the two lifecycles meet in south-western France. The biology of oak gallwasps predicts that any hybrid zone will be narrow and limited to regions where Q. cem's and Q. suber meet. Our data suggest that eastern and western A. kollari are effectively separate species.
From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL accession-num: 11298986
Keywords: Alleles; Andricus; Animals; Base Sequence; Cellulose Acetate; Cytochrome b Group; Cytochrome b Group: chemistry; Cytochrome b Group: genetics; DNA; Electrophoresis; Environment; EUROPE; Evolution; Female; gallwasp; Genetic Variation; Genetic Variation: physiology; glacial refugia; host race; Hymenoptera; Hymenoptera: genetics; Hymenoptera: growth & development; Hymenoptera: physiology; invasion; Life Cycle Stages; Mitochondrial; Mitochondrial: chemistry; Mitochondrial: isolation & purification; Molecular; Molecular Sequence Data; Parthenogenesis; phylogeny; Polymerase Chain Reaction; range expansion; Sequence Alignment; Sequence Analysis